Главнейшие вопросы развития прикладной энтомологии на Украине - Крышталь, А.Ф. (Вестник зоологии, 1971)
The article is devoted to the problems of entomology development in the Ukraine during the ninth five-year plan. An opinion is advanced on the necessity to improve coordination of research work and economical substantiation of the developed subjects. Some problems are outlined, the solution of which is of primary importance for plant, animal and human protection from parasites, pests and vectors of disease agents.